The Five-Dimensional Influencer Marketing Model and Its Impact on Digital Natives’ Purchase Decisions - Ahyar Junaedi (Research Synergy Foundation, 2026)
This study examines how influencer credibility and content characteristics influence purchase decisions in digital consumer environments, while incorporating the moderating roles of social media interaction and platform preference. The research adopts a quantitative approach, using Partial Least Squares Structural Equation Modeling (PLS-SEM), to analyze the hypothesized structural relationships within a multidimensional influencer marketing framework. Data were collected from 513 active social media users in Indonesia who regularly engage with influencer-generated content across major digital platforms, selected through purposive sampling to ensure relevant exposure. The findings reveal that content relevance, platform preference, and social media interaction significantly influence purchase decisions. In contrast, influencer credibility and content frequency do not demonstrate significant effects, indicating a shift in digital consumer behavior toward content-driven and platform-oriented evaluation. Furthermore, the moderating effects of social media interaction and platform preference are not supported, suggesting that these variables serve more as direct predictors than as amplifying mechanisms. This study contributes to the literature by proposing a five-dimensional influencer marketing model that integrates influencer attributes, content characteristics, user interaction, and platform context within a single analytical framework. The results highlight that influencer effectiveness is increasingly shaped by message relevance and platform familiarity rather than traditional credibility factors. From a practical perspective, marketers are encouraged to prioritize relevant content, select appropriate platforms aligned with audience behavior, and foster meaningful interaction, rather than relying solely on influencer popularity or posting intensity.